'Cyclo-Photographers', Visual Modernity, and the Development of Camera Technologies, 1880s–1890s. Issue 1 (2nd January 2018) - Dominici, Sara
Abstract : The intertwined development of popular photography and cycling in Britain was felt so close that, in the 1880s, contemporary commentators could write of 'cyclo-photographers'. The camera apparatus available at this time, bulky and fragile, was largely impractical to carry on a ride, and thus cyclo-photographers joined outdoor photographers in asking manufacturers for simpler and easier to operate cameras. However, a close reading of primary sources reveals that such demands were also the result of a new engagement with the possibility of seeing enabled by cycling itself. What was the cyclo-photographers' experience of visual modernity? This article explores whether, and in what ways, the parallel emergence of a desire for compact cameras was linked to the new, and interconnected, ways of moving and seeing that the engagement with these two modern cultural technologies had made possible.